Size of business unit as a factor influencing adoption of digital marketing: Empirical analysis of SMEs operating in the Central European market - František Pollák; Peter Markovič (Administrative Sciences, 2021)
The issue of using marketing communication tools in the internet environment is quite extensive. Innovation of the usual procedures is usually influenced by market development. The presented study examines selected factors that may affect the acceptance of digital marketing tools in business practice in small and medium-sized enterprises (SMEs). The aim of the study is to answer the basic question of whether company size influences the willingness to adopt online marketing tools within the usual communication mix. Based on a thorough empirical analysis performed on a sample of companies operating in the Central European market, it can be stated that company size does not play a role in adopting online marketing tools. Most organizations, regardless of their size, still have reservations about investing in digital marketing. On the other hand, previous experience is a key determinant to perceive the benefits of using the internet for business purposes. Organizations actively using online marketing tools evaluate their contribution to their business very positively. It is a well-known fact that product testing significantly increases the degree of its acceptance. This knowledge is one of the key starting points in traditional marketing. Obviously, this assumption needs to be taken into account in both physical and digital environments. At the same time, it should be noted that the application of the basic online marketing tools in business practice is a prerequisite for all subsequent online activities.
Keywords: 350; competitiveness; e-marketing; electronic marketing; family businesses; innovations; internet; online marketing; small and mid-size enterprises